Reproductive aspects of the one-sided livebearer Jenynsia multidentata (Jenyns, 1842) (Cyprinodontiformes) in the Patos Lagoon estuary, Brazil - Mai, Ana Cecilia Giacometti (2007)
Jenynsia multidentata (Jenyns, 1842) is a viviparous fish found year-round in the estuary zone of Patos Lagoon and represents one of the dominant species in its shallow areas. Although biological and ecological aspects of the J. multidentata's population occurring in Patos Lagoon estuary have been previously investigated, there is no published information regarding itsreproductive biology in this estuarine area. The reproductive cycle of this species in the estuarine zone of Patos Lagoon occurred from September to May, showing a positive correlation with water temperature (r = 0.76). The sexual ratio in the estuary was 1.98/1 (female/male) and female size and fecundity had a positive correlation. It was observed that J. multidentata presented a second pregnancy during January and February months, which has not been described in previous studies.